2012
DOI: 10.1002/lnc3.317
|View full text |Cite
|
Sign up to set email alerts
|

Representing Motion in Language Comprehension: Lessons From Neuroimaging

Abstract: A central issue in understanding how language links the mental and the real world is the nature of the mental representations entertained during language processing. Are these mental representations closely linked to the perceptual experiences from which they were formed or are they somewhat removed from them? This review addresses this question by examining studies that have investigated motion verbs and sentences using functional magnetic resonance imaging. These studies tested whether language processing el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 89 publications
(105 reference statements)
1
13
0
Order By: Relevance
“…As Taylor and Zwaan (2009) wrote to account for neuropsychological data on action-related word processing: “(…) comprehension relies on a multivariegated system for conceptual representation that relies on experiential memory (including motor, sensory, and intuitive experiential traces).” In addition, the top-down effect produced by the strategy use is strengthened now by neuroimaging evidence linking the visual-semantic motion features of action verbs/sentences with the left posterolateral temporal cortex (for a review, see Gennari, 2012). In this domain too it is held that modality-specific brain regions processing visual motion such as the middle temporal area or area V5 are not automatically or habitually engaged in language processing (Gennari, 2012). The lack of V5 activation in tasks in which motion information must be recruited suggests that V5 activation in is not integral to motion content processing per se , but rather it results from top-down influences or selective attention (Gennari, 2012).…”
Section: Mental Rotation and Action-related Word Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…As Taylor and Zwaan (2009) wrote to account for neuropsychological data on action-related word processing: “(…) comprehension relies on a multivariegated system for conceptual representation that relies on experiential memory (including motor, sensory, and intuitive experiential traces).” In addition, the top-down effect produced by the strategy use is strengthened now by neuroimaging evidence linking the visual-semantic motion features of action verbs/sentences with the left posterolateral temporal cortex (for a review, see Gennari, 2012). In this domain too it is held that modality-specific brain regions processing visual motion such as the middle temporal area or area V5 are not automatically or habitually engaged in language processing (Gennari, 2012). The lack of V5 activation in tasks in which motion information must be recruited suggests that V5 activation in is not integral to motion content processing per se , but rather it results from top-down influences or selective attention (Gennari, 2012).…”
Section: Mental Rotation and Action-related Word Processingmentioning
confidence: 99%
“…In this domain too it is held that modality-specific brain regions processing visual motion such as the middle temporal area or area V5 are not automatically or habitually engaged in language processing (Gennari, 2012). The lack of V5 activation in tasks in which motion information must be recruited suggests that V5 activation in is not integral to motion content processing per se , but rather it results from top-down influences or selective attention (Gennari, 2012). As it happens for the M1 cortex, the middle temporal area or area V5 is susceptible to top-down control and higher-level perceptual/conceptual influences: implied motion, apparent and illusory motion, “moving” sounds, and imagined motion can all elicit significant levels of activation in this area (Gennari, 2012).…”
Section: Mental Rotation and Action-related Word Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is individual variability in the vividness with which people are able to picture scenes in “their mind’s eye” (e.g., Cui et al, 2007). This variability seems to be related to experience (Isaac and Marks, 1994; Sadoski and Paivio, 2001; Gennari, 2012). As leisure readers are expected to have more experience with books and with building mental models that support story comprehension, we will examine whether they are more likely to engage in mental imagery than non-leisure readers.…”
Section: Introductionmentioning
confidence: 95%
“…In keeping with the first prediction, a number of studies employing either positron emission tomography (PET) or functional magnetic resonance imaging (fMRI) have shown that the PLTC is significantly engaged, more strongly in the left than the right hemisphere, when people process the meanings of action verbs, relative to when they perform various baseline tasks (for a review, see Gennari 2012, and for representative studies see Damasio et al 2001;Kable et al 2002Kable et al , 2005Noppeney et al 2005;Tranel et al 2005;Kemmerer et al 2008;Pirog Revill et al 2008;Pulvermüller et al 2009;Lin et al 2011).…”
Section: Activation Patternsmentioning
confidence: 93%